TRADISI KEINTELEKTUALAN PEMIKIRAN DAN BIOGRAFI ABDURRAHMAN WAHID (GUS DUR) - Firdaus Syah (Pascasarjana UIN Sumatera Utara, 2021)
In Abdurrahman Wahid's perspective, Islamic education is an inseparable unit because each other has a reasonably close relationship in developing future Islamic education. According to Gus Dur, Islamic education is a process to deliver students with sufficient provisions and think critically throughout their lives. In Gus Dur's perspective, Islamic education is a combination of traditional Islamic education thinking and Islamic thought adopted by modern Western thought so that it can give birth to an educational system in the concept of renewal, by the demands of the times. The purpose of Islamic education to humanize humans is an absolute thing. Education in Islam is a series of processes of human empowerment towards being active (maturation), to carry out the human function that is carried out as a servant before the creator and as a custodian (caliphate) in the universe. Thus, the ultimate goal of Islamic education is to form students' self to fit the nature of their existence.